2016
DOI: 10.1177/1741143216665838
|View full text |Cite
|
Sign up to set email alerts
|

The role of governing bodies in the management of financial resources in South African no-fee public schools

Abstract: The National Norms and Standards for School Funding policy was adopted by the government to address equity in South African public schools. This pro-poor funding policy compels the state to progressively fund schools based on a quintile ranking system. Schools lacking in infrastructure, physical and financial resources and usually located within poor socio-economic environments are ranked quintiles 1 and 2. These schools are referred to as no-fee schools and are provided with far more state funding than well-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 5 publications
0
18
1
2
Order By: Relevance
“…However, financial literacy does not significantly moderate the relation between IC and resource acquisition, which does not support H7. Unlike Mestry [70] and Yang, Ishtiaq, and Anwar [49], who demonstrated a significant role of financial literacy in managing and utilizing resources, we found that financial literacy does not significantly help top managers to acquire rare, unique, and immutable resources. Senior managers of Pakistani firms likely have low financial literacy, which may hinder their venture's growth.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, financial literacy does not significantly moderate the relation between IC and resource acquisition, which does not support H7. Unlike Mestry [70] and Yang, Ishtiaq, and Anwar [49], who demonstrated a significant role of financial literacy in managing and utilizing resources, we found that financial literacy does not significantly help top managers to acquire rare, unique, and immutable resources. Senior managers of Pakistani firms likely have low financial literacy, which may hinder their venture's growth.…”
Section: Discussioncontrasting
confidence: 99%
“…Financial literacy can facilitate better usage of governing skills and practices to use financial resources effectively. In contrast, governing bodies lacking literacy face difficulty in using financial resources [70] efficiently. Firms need to reduce different types of costs related to operation, supplies, and sales to improve their competitive performance.…”
Section: The Moderating Role Of Financial Literacymentioning
confidence: 99%
“…En este mismo sentido, Coccia & Rolfo (2013) mencionan que las debilidades organizativas y las amenazas económicas para los centros de investigación públicos son generadas por la política de investigación basada en la reducción de los presupuestos y la reducción del personal de investigación. Aunado a lo anterior, las IES y sus centros de investigación experimentan numerosos desafíos en la gestión eficaz de los fondos, un ejemplo son sus órganos rectores que carecen de habilidades financieras y empresariales (Mestry, 2018). Así entonces, la planificación de la investigación parece ser una práctica desatendida particularmente en países económicamente desfavorecidos (Nguyen ISSN online 2007-9621 Peinado Camacho, J., Montoy Hernández, L. D., & Torres Hernández, Z. Estrategia de gestión para la generación de recursos en un centro de investigación y posgrado.…”
Section: Marco Teóricounclassified
“…Hence, unlike most of the universities across the globe, the USA does not rely on short-term grants of government funding. Even South African schools having infrastructural issues, lacking physical or financial resources and being located in poor socio-economic regions are considered as ‘no-fees’ schools, and can get more funding from the state government as compared to other well-off schools (Mestry, 2018). However, even in the most industrialized and wealthiest developing nations, academe faces intense fiscal problems (Teferra and Altbach, 2004).…”
Section: Indian Context and Challengesmentioning
confidence: 99%
“…However, even in the most industrialized and wealthiest developing nations, academe faces intense fiscal problems (Teferra and Altbach, 2004). Weak capacity of the state to fund HE hinders effective financial management of schools (Mestry, 2018).…”
Section: Indian Context and Challengesmentioning
confidence: 99%